Low-dose paclitaxel modulates the cross talk between the JNK and Smad signaling in primary biliary fibroblasts - Lu,Jiamei (2022)
SUMMARY OBJECTIVE: The objective of this study was to explore the molecular mechanism underlying the occurrence of benign bile duct stricture and the target of low-dose paclitaxel in the prevention of benign bile duct stricture. METHODS: Under the stimulation of transforming growth factor beta 1, the expression of collagen type I and connective tissue growth factor were detected on isolated primary fibroblasts. The phosphorylation levels of JNK and Smad2L were detected using Western blot. The effect of low-dose paclitaxel on the transforming growth factor beta 1-induced inhibition of type I collagen and connective tissue growth factor expression and JNK and Smad2L phosphorylation was also observed. RESULTS: Transforming growth factor beta 1 induced the secretion of type I collagen and connective tissue growth factor as well as JNK phosphorylation in biliary fibroblasts. The JNK inhibitor or siRNA-Smad2 inhibited the transforming growth factor beta 1-induced secretion of type I collagen and connective tissue growth factor. Low-dose paclitaxel inhibited the expression of type I collagen induced by transforming growth factor beta 1 and may inhibit the secretion of collagen in biliary fibroblasts. CONCLUSION: The activation of JNK/Smad2L induced by transforming growth factor beta 1 is involved in the occurrence of benign bile duct stricture that is mediated by the overexpression of type I collagen and connective tissue growth factor, and low-dose paclitaxel may inhibit the phosphorylation of JNK/Smad2L.